To solve the equation \( 3(2 - m) = 12 - m \), follow these steps:
-
Distribute the 3 on the left side: \[ 3 \cdot 2 - 3 \cdot m = 6 - 3m \] So the equation becomes: \[ 6 - 3m = 12 - m \]
-
Next, let's rearrange the equation to isolate \( m \). We can add \( 3m \) to both sides: \[ 6 = 12 - m + 3m \] This simplifies to: \[ 6 = 12 + 2m \]
-
Now, subtract 12 from both sides: \[ 6 - 12 = 2m \] So we have: \[ -6 = 2m \]
-
Finally, divide both sides by 2: \[ m = \frac{-6}{2} = -3 \]
Thus, the solution to the equation is: \[ m = -3 \]